DETERMINAN PENENTUAN NILAI PROPERTI DI KOTA KENDARI - Nurhasanah Nurhasanah; Hairudin Bugis; Al Asy Ari Adnan Hakim (Universitas Muhammadiyah Kendari, 2023)
ABSTRACTThis study aims to explore the factors that determine the value of residential properties in Kendari City. The type of research used is quantitative with an exploratory design. The population of the study consists of all residential properties in Kendari City, which are infinite in nature, with the sample determined using a convenience sampling technique totaling 39 housing units of type 36. The research data consist of primary data, namely direct observations related to the physical size of the property, as well as secondary data obtained from documentation and mapping through Google Maps. Data collection methods were carried out using questionnaires and documentation, while data analysis employed Exploratory Factor Analysis (EFA), which included validity and reliability tests, KMO, Bartlett’s Test, and factor rotation. The results of the study show that out of 13 variables tested, 9 variables met the requirements for factor analysis, and from the analysis, 3 main factors determining property value in Kendari City were identified: (1) distance factor, which includes distance to markets, health services, and educational facilities; (2) room size factor, which includes the size of the living room and bathroom; and (3) land potential and property area factor, which includes side land surplus, land area, building age, and the number of schools around the location. These findings affirm that property value is multidimensional and influenced by a combination of spatial, structural, and environmental factors.